Knowledge is power. (Therapy Today, 2026)
The article highlights various new podcasts that explore diverse and meaningful topics. Emma Barnett's podcast, "Ready to Talk," addresses subjects such as likability, perfectionism, and perimenopause, showcasing her direct conversational style. Comedians Mo Gilligan, Babatunde Aléshé, and Eddie Kadi collaborate in "Man Like You," where they discuss boundaries, friendship, and male pride, touching on personal experiences and therapy. Additionally, "All in the Mind" features a discussion on the effectiveness of trigger warnings and includes insights from therapist Stephen Grosz about love, based on his book "Love's Labour."